NEMIS VA O‘ZBEK TILLARI LEKSIKASIDA GENDER TAHLILI (Journal of Universal Science Research, 2025)
This article analyzes gender-related vocabulary in German and Uzbek, highlighting their linguistic structures and the role of language in shaping social perceptions of gender. German has a grammatical gender system that explicitly distinguishes between masculine, feminine, and neutral forms, including occupational titles. In contrast, Uzbek lacks grammatical gender but exhibits lexical gender differences, often associating certain professions with men. Modern linguistic trends in both languages reflect efforts toward gender inclusivity, with German incorporating gender-neutral forms and Uzbek gradually adopting gender-specific occupational terms. This comparative analysis provides insight into how languages reinforce or challenge gender norms.